Las crisis financieras de la globalización. (2014)
In the twentieth century there was a debate between Keynesian and the market neoliberal economy school and the Keyneysian model prevail until the arrival of contemporary globalization,that adopted the neoliberal paradigm. Instead of a productive globalization a financial globalization was first developed which has led to recurring crises since 1929; the last one erupted in 2008 and it is still having a negative impact on the economic environment of the planet. The result has been to produce a very slow market self-regulation of the neoliberal model by introducing again monitoring and follow-up mechanisms by States and international organisms for predicting the occurrence of such serious crises for world economy.